Biological role of zonulin: a biomarker of increased intestinal permeability syndrome - A. I. Khavkin (Rossijskij Vestnik Perinatologii i Pediatrii, 2021)
.Both changes in diet and pathological conditions caused by an infectious agent, allergic or autoimmune inflammatory process, affect the biological rhythms of the digestive tract, which negatively affects the intestinal microbiota and increases the permeability of the intestinal mucosa. The altered microbiota potentiates inflammation and causes a “vicious circle”. The zonulin protein is the agent that modulates the density of intercellular connections. The review presents data on the biological role of zonulin, correction of its synthesis violation with the help of functional products for baby food.